Curva de sobrevivência e estimativa de entropia em Lucilia cuprina (Diptera, Calliphoridae) - Fernandes, Francely M. [UNESP]; Lapola, David M. [UNESP]; Neregato, Rodrigo [UNESP]; Carvalho, Marcelo H. de [UNESP]; Von Zuben, Claudio J. [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2003)
Lucilia cuprina (Wiedemann, 1830) is a cosmopolite blowfly species of medical and veterinary importance because it produces myiasis, mainly in ovine. In order to evaluate the demographic characteristics of this species, survivorship curves for 327 adult males and 323 adult females, from generation F1 maintained under experimental conditions, were obtained. Entropy was utilized as the estimator of the survival pattern to quantify the mortality distribution of individuals as a function of age. The entropy values 0.216 (males) and 0.303 (females) were obtained. These results denote that, considering the survivorship interval until the death of the last individual for each sex, the males present a tendency of mortality in more advanced age intervals, in comparison with the females.
Survivorship curve and estimate of entropy in Lucilia cuprina (Diptera, Calliphoridae)
Keywords: Survivorship curve; entropy; Lucilia; Calliphoridae